Clarifications and Proposals for Improvement in Romanian Accounting Regulations on Profit Distribution / Cover Loss and Presentation of Information Appropriate - Rotila, Aristita (Studies and Scientific Researches. Economics Edition, 2010)
Starting from the analysis of accounting regulations in compliance with European directives applicable to the different categories of entities, as well as from the findings of a study we carried out concerning the financial statements of certain economic agents, in this paper we intend to signal some aspects which, in our opinion, require clarifications, and to launch some proposals leading to the improvement of Romanian accounting regulations, even though these will still be applied over a period of time.